1987
DOI: 10.1111/j.1432-1033.1987.tb10600.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change accompanies redox reactions of the tetraheme cytochrome c-554 of Nitrosomonas europaea

Abstract: Cytochrome c-554 of the ammonia-oxidizing chemolithoautotropic bacteria is thought to mediate electron transfer from hydroxylamine oxidoreductase to a terminal oxidase and/or to ammonia monooxygenase. The cytochrome has four c hemes which interact magnetically and have the same redox potential.We report that the kinetics of reduction of ferric cytochrome c-554 by dithionite or the oxidation of ferrous cytochrome c-554 by O2 or H 2 0 2 are complex and multiphasic. Transient rapid-scan difference spectra indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Finally, using the < values at 419 nm from Table III, a 2:1 ratio of amplitudes would have been expected on the basis of this revised interpretation. This is reasonably close to the ratio observed in several of the figures presented previously (DiSpirito et al, 1987).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, using the < values at 419 nm from Table III, a 2:1 ratio of amplitudes would have been expected on the basis of this revised interpretation. This is reasonably close to the ratio observed in several of the figures presented previously (DiSpirito et al, 1987).…”
Section: Discussionsupporting
confidence: 92%
“…A previous report investigating the kinetics of reduction of ferric cytochrome c554 by dithionite used rapid-scan absorption spectra in an attempt to differentiate hemes in cytochrome c554 (DiSpirito et al, 1987). The data suggested that there were distinct spectral bands hidden within the unusually broad Soret and a bands reported for this protein.…”
Section: Discussionmentioning
confidence: 93%
“…These observations suggest that the observed structural changes are significant and not associated with inherent flexibility of cyt c554 in that region. This conformational change may contribute to the biphasic kinetics observed upon dithionite reduction [25].…”
Section: Oxidation-state-dependent Structural Changesmentioning
confidence: 98%
“…Whether the oxidation of hydroxylamine also provides reductant for ammonia (or methane) oxidation or whether all four electrons are transferred to the terminal oxidases (21,62) via cytochrome cЈ (64) and cytochrome c 555 (5) has not been determined for methanotrophs. In the nitrifying bacterium Nitrosomonas europaea, the four electrons from the oxidation of hydroxylamine are transferred to the tetraheme cytochrome, cytochrome c 554 , which acts as a redox mediator from hydrox-ylamine oxidoreductase to both the ammonia monooxygenase and the terminal oxidase (17,33). In the current study, we present the isolation of an octyl-heme cytochrome, cytochrome c 553O .…”
mentioning
confidence: 99%